DECISION SUPPORT SYSTEM FOR SELECTION OF CHAIRMAN OF OSIS USING ELECTRE METHOD IN SMK PGRI 35 WEST JAKARTA - Mia Rosmiati; Nur Atika Sari (Jurnal Techno Nusa Mandiri, 2020)
In an organization choosing a leader who is highly dedicated, responsible and responsive to every problem is not easy. A leader is not only required to have intelligence and skill but also must have a soul of leadership, a great sense of responsibility and can be a role model. The purpose of this study was to determine the student council president using the ELECTRE method based on 4 (four) criteria, namely managerial ability, knowledge and skills, collaborative communication responsibilities and discipline. With the application of the ELECTRE method, it is expected to be able to achieve these objectives. With the implementation of the ELECTRE method in the process of electing the student council president at SMK PGRI 35 Jakarta, it can determine the student council chair with accurate results in accordance with the criteria given by the school. The results of calculations with the Electre method will obtain the highest rating, namely: A3 (Miranti Sofia) because if it indicates that the alternative is the chosen alternative.